The Effect of Spiritual Qur’anic Emotional Freedom Technique (SQEFT) Therapy on Reducing Anxiety Value and Blood Cortisol Levels in NAPZA (Narcotics, Psychotropic, Other Addictive Substances) Residents - Asmawati, Veny Hadju; Alimin Maidin; Andi Ummu Salmah; Ridwan Amiruddin; Aminuddin Syam; Muh.Tahir Abdullah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The patients in general and, in particular, the patients of drug/NAPZA (Narcotics,Psychotropic, and Other Addictive Substances) residents seek spiritual support during illness and undergorehabilitation. Both religion and spirituality are related to positive coping mechanisms (psychological)and exercise (physical). NAPZA (drug) residents undergoing rehabilitation experience anxiety, includingmoderate anxiety and severe anxiety, which can adversely affect physical and mental disorders. Thisresearch aims to determine the effect of Spiritual Qur’anic Emotional Freedom Technique (SQEFT) therapyon reducing anxiety values and blood cortisol levels in NAPZA residents. Method: The experiment wasused with a pre-post control group design, and purposive sampling was as the sampling technique. Thisresearch was conducted at Mandatory Report Recipient Institution (IPWL) Pelita Jiwa Insani Foundationin Padang, consisting of 44 respondents who were divided into two groups, namely the experimental group(n=24) and the control group (n=20). Data were collected using the Hamilton Rating Scale questionnaire todetermine the reduction in anxiety values and venous blood sampling for measuring blood cortisol levels.Data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney test. Results and Analysis:the results of the research on the anxiety variable obtained p-value = 0.004 (p<0.05), which means that thereis a significant difference given the Spiritual Qur’anic Emotional Freedom Technique (SQEFT) therapy inreducing the value of anxiety in NAPZA residents currently undergoing rehabilitation. The cortisol variableresults showed p=0.00 (p<0.05), so it can be interpreted that there is a significant difference in the differencevalue of cortisol in reducing blood cortisol levels in NAPZA residents who are undergoing rehabilitation.Discussion and Conclusion: There is a significant effect of giving Spiritual Qur’anic Emotional FreedomTechnique (SQEFT) therapy on reducing anxiety values and blood cortisol levels in NAPZA residents.